Benign course and clinical features of COVID‐19 in hospitalised febrile infants up to 60 days old. (30th June 2021) - Yarden Bilavski, Havazelet; Balanson, Sarit; Damouni Shalabi, Ranaa; Dabaja‐Younis, Halima; Grisaru‐Soen, Galia; Youngster, Ilan; Glikman, Daniel; Ben Shimol, Shalom; Somech, Eli; Tasher, Diana; Stein, Michal; Gottesmanm, Giora; et al.
Abstract: Aim: Minimal data exist regarding the severity of COVID‐19 in febrile infants under 60 days old. This multicentre prospective study explored the clinical course and outcomes of this hospitalised patient population, as, to date, the best approach has not been specifically addressed. Methods: This study focused on the clinical features, laboratory parameters and outcomes of febrile infants up to 60 days old who tested positive for the virus and were hospitalised in Israel from March 2020 to January 2021. The data were extracted from a real‐time prospective surveillance network for COVID‐19 that includes 20 of the country's 26 hospitals. Results: We identified 75 febrile young infants (60% female) with COVID‐19 at a median age of 28 days (range 8–56 days). Of these, 84% had an unremarkable medical history, 29% had respiratory symptoms, and 96% had a mild illness. The Rochester criteria showed that 44% were considered at high‐risk for serious bacterial infections, and we found that eight infants actually had concomitant bacterial infections. Outcomes were excellent, and no complications or fatalities were reported. Conclusion: The excellent outcomes of young febrile infants with COVID‐19 closely resembled other respiratory viral aetiologies of fever in this age group, and there were no fatalities.